(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Cardiovascular diseases are one of the most important causes of morbidity and mortality in the world today. Along with classical risk factors like dyslipidemia, hypertension, Diabetes mellitus and familial history of Coronary Artery Disease (CAD) modifiable risk factors like smoking and alcohol are significantly contributing to the statistics in young adults with acute myocardial infarction (AMI). Objective: To study the clinical profile and assess the modifiable and non-modifiable risk factors of AMI in young adults. Methods: All patients aged ≥18yrs and ≤40yrs hospitalized with Acute Myocardial Infarction (AMI) from 2013 to 2015 are evaluated for clinical profile, risk factors & outcome. Results: Of the 50 patients mean age was 37.44yrs (±3.69), and males were more than the females with a ratio of 21:4. All patients presented with the chief medical symptom of chest pain and most patients had a combination of risk factors like dyslipidemia, hypertension, and diabetes mellitus. Smoking is found to be the most important independent risk factor in young males (93%). Anterior wall AMI was the predominant diagnosis, complications were very less with mortality of only 3%. The LVEF was very good on 2-D-Echocardiography (76% > 40). Conclusion: Younger patients have an excellent long-term and short-term prognosis because of their better baseline characteristics, thus requiring a different line of management concerning the older age group. Therefore it is important to highlight the modifiable and non-modifiable risk factors in young adults so as to have a better prognosis and higher life expectancy.